Research on the influence of pore parameters of carbon aerogel on infrared interference performance - Guan, Zhichao; Guo, Aiqiang; Li, Tianpeng; Zhai, Jiangjiang; Gao, Xinbao (Frontiers in Materials, 2025)
The porosity parameter is one of the characteristic parameters of carbon aerogel, and the porosity and pore size distribution affect the infrared interference performance of carbon aerogel. In this study, nine types of carbon aerogel samples were selected to characterize and evaluate their micromorphology, particle size distribution, and porosity parameters. The objective was to obtain the characteristic parameters related to particle size distribution, porosity, and pore size distribution for these nine carbon aerogel samples. The infrared interference performance of nine types of carbon aerogel samples was evaluated in a smoke box. The analysis focused on the influence of porosity and pore size distribution on the interference performance across the infrared bands of 1–3 μm, 3–5 μm, and 8–14 μm. The results indicate that carbon aerogel exhibits a strong extinction effect across the three infrared bands. The increase in porosity leads to a higher infrared extinction coefficient, while an increase in average pore diameter can also enhance the infrared extinction coefficient.